Численно-полевой анализ электромагнитных процессов в роторе турбогенератора при несимметричной нагрузке - Милых, В.И. (Технічна електродинаміка, 2017)
На основе многопозиционных численных расчетов вращающегося магнитного поля проведена оценка работы ротора турбогенератора при несимметрии нагрузки в рамках ее стандартных ограничений. Результаты расчетов при несимметричной нагрузке, проведенные на примере турбогенератора мощностью 35 МВт, сопоставлены с аналогичными результатами при симметричной нагрузке. Проанализированы форма и гармонический состав ЭДС в обмотке ротора и в его пазовых клиньях, дана оценка токов, вызванных этими ЭДС. Рассмотрены также временные функции переменной составляющей магнитной индукции на поверхности вращающегося ротора. На основі багатопозиційних чисельних розрахунків обертового магнітного поля виконана оцінка роботи ротора турбогенератора при його несиметричному навантаженні у межах її стандартних обмежень. Результати розрахунків при несиметричному навантаженні, проведені на прикладі турбогенератора потужністю 35 МВт, зіставляються з аналогічними результатами при симетричному навантаженні. Аналізуються форма і гармонійний склад ЕРС в обмотці ротора і його пазових клинах, дано оцінку струмів, викликаних цими ЕРС. Розглядаються також часові функції змінної складової магнітної індукції на поверхні обертового ротора. The estimation of the turbo-generator rotor work was conducted under turbo-generator unbalanced loading within the framework of its standard limitations on the basis of the multi-position numerical calculations of the rotating magnetic field. The results of calculations at the asymmetrical loading which were carried out by the example of 35 MW turbogenerator are compared with similar results with symmetrical loading. The form of temporal functions and harmonic composition of the EMF in the rotor winding and in its slot wedges are analyzed, the estimation of currents caused by these EMF is done. Level of the variable EMF in the field winding is very significant, however the variable component of current in it isn't a serious problem. EMF in the rotor wedges reach tens of volts, currents - of the order of 2.5 kA, and in different wedges they differ markedly. The temporal functions of the magnetic induction variable component on the surface of the spinning rotor, whose values increase significantly because of the unbalanced load, are also examined.